Bacillus spore germination at moderate high pressure: A review on underlying mechanisms, influencing factors, and its comparison with nutrient germination. Issue 4 (19th June 2021) - Delbrück, Alessia I.; Zhang, Yifan; Heydenreich, Rosa; Mathys, Alexander
Abstract: Spore‐forming bacteria are resistant to stress conditions owing to their ability to form highly resistant dormant spores. These spores can survive adverse environmental conditions in nature, as well as decontamination processes in the food and related industries. Bacterial spores may return to their vegetative state through a process called germination. As spore germination is critical for the loss of resistance, outgrowth, and development of pathogenicity and spoilage potential, the germination pathway has piqued the interest of the scientific community. The inhibition and induction of germination have critical applications in the food industry. Targeted germination can aid in decreasing the resistance of spores and allow the application of milder inactivation procedures. This germination‐inactivation strategy allows better maintenance of important food quality attributes. Different stimuli are reported to trigger germination. Among those, isostatic high pressure (HP) has gained increasing attention due to its potential applications in industrial processes. However, pressure‐mediated spore germination is extremely heterogeneous as some spores germinate rapidly, while others exhibit slow germination or do not undergo germination at all. The successful and safe implementation of the germination‐inactivation strategy, however, depends on the germination of all spores. Therefore, there is a need to elucidate the mechanisms of HP‐mediated germination. This work aimed to critically review the current state of knowledge on Bacillus spore germination at a moderate HP of 50–300 MPa. In this review, the germination mechanism, heterogeneity, and influencing factors have been outlined along with knowledge gaps.